2013
DOI: 10.1080/15287394.2013.821962
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection ofToxoplasma gondiiin Water Sources of District Nowshehra, Khyber Pakhtunkhwa, Pakistan

Abstract: Toxoplasmosis is spread through contamination of water sources and results in morbidity globally. In the current study 300 water samples were processed by polymerase chain reaction (PCR) for detection of Toxoplasma gondii. The overall prevalence in different water sources was 6.6% (17/300). Among different water sources the highest prevalence was recorded in drain water at 7% (7/100), followed by tube well water at 7.5% (3/40) and open well water at 5% (5/100) ,and the lowest was recorded in tap water at 3.33%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…An alternative explanation may be that people acquire T. gondii infection through contaminated environments in the community, regardless of their occupation/educational level. In this study, no gender difference was found associated with the seroprevalence of T. gondii, supporting observations made elsewhere (34) (35) (37) . High LA titers of sera anti-Toxoplasma antibodies are regarded as an indicator of either acute or new infection with T. gondii (38) .…”
Section: Discussionsupporting
confidence: 80%
“…An alternative explanation may be that people acquire T. gondii infection through contaminated environments in the community, regardless of their occupation/educational level. In this study, no gender difference was found associated with the seroprevalence of T. gondii, supporting observations made elsewhere (34) (35) (37) . High LA titers of sera anti-Toxoplasma antibodies are regarded as an indicator of either acute or new infection with T. gondii (38) .…”
Section: Discussionsupporting
confidence: 80%
“…Our study results of T. gondii in water samples agree with those reported in Pakistan, which revealed 7% positive samples ( Khan et al, 2013 ), 12.5% in Bulgaria ( Kourenti and Karanis, 2006 ), and 13% in Norway with real-time PCR ( Harito et al, 2017 ). In contrast, studies conducted in Greece ( Kourenti and Karanis, 2006 ) and Nariño, Colombia ( Sanchez et al, 2014 ) yielded no positive results for T. gondii .…”
Section: Discussionsupporting
confidence: 90%
“…The DNA was amplified through polymerase chain reaction (PCR) using primer specific for Fasciola hepatica ( Figure 2 ). The primer added for F. hepatica was -F, 5′-AGTGATTACCCGCTGAACT-3′, and R, 3′-CTGAGAAAGTGCACTGACAA-5′ [ 13 ]. The specific amplified product was compared with 100 bp DNA ladder marker (Fermentas, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In tropical countries, fasciolosis is considered the single most important helminthes infection of cattle, with reported prevalence of 30–90%. In domestic ruminants, adverse effects of acute or chronic fasciolosis include decreased meat and milk production, decreased fertility, and increased veterinary costs [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%